The Use of Counseling About Complementary Feeding in Families in Fulfilling the Nutritional Needs of Children aged 6-24 Months : A Literature Review - Arifa, Yeni Zanuba; Susanto, Tantut; Rasni, Hanny; Fauziah, Wahyuni (Journal of Rural Community Nursing Practice, 2024)
Background: Malnutrition remains a significant nutritional challenge for children under five. The active involvement of families, particularly parents, is crucial in meeting the nutritional needs of children. The intake of nutrients from complementary feeding plays a vital role in meeting the nutritional requirements, especially for children aged 6-24 months. Therefore, family-based therapy, facilitated through counseling, is essential to empower families in addressing children's nutritional issues. This approach aims to enhance the practice of complementary feeding, thereby preventing nutritional problems and fostering the growth and development of children. Purpose: This literature study described the use of counseling on complementary feeding to families in fulfilling the nutritional needs of children aged 6-24 months. Methods: The research design used in this study was a narrative literature review. Search articles through 4 databases (Google Scholar, ScienceDirect, PubMed, and SpringerLink) and keywords family counseling, complementary feeding, and children aged 6-24 months. Articles were searched through 4 stages based on the PRISMA flowchart. Results: The analysis of ten articles in this study revealed that the implementation of complementary feeding counseling when tailored to the specific needs and circumstances of the family, has a significant and positive impact on changing family behavior related to complementary feeding practices. This includes attention to the method, media, steps, and implementation time and identifying the right target, which could be the primary caregiver or the entire family unit. Such interventions have improved adherence to standards and recommendations, increasing children's weight and nutritional status. Conclusions: Family counseling on complementary feeding significantly enhances the knowledge, attitudes, and behaviors related to mothers' complementary feeding practices. When these practices align with the standards and recommendations set by health authorities, they can effectively meet the nutritional needs of children aged 6-24 months. When achieved, this alignment empowers the audience to play a crucial role in promoting children's optimal growth and development.